The Role of Chinese Small and Medium TNCs in the Modernization of the National Economy - D. B. Kalashnikov (Vestnik MGIMO-Universiteta)
Why does the Chinese economic modernization strategy include transnationalization of Chinese enterprises, the creation of numerous Small and Medium Foreign Affiliates (SMFAs)? The research hypothesis suggests that in the context of globalization, modernization requires influencing other participants in the global economy beyond national borders. SMFAs are able to transform the structure of the economy of the PRC and host countries to ensure demand for national innovations and highly skilled labor. The literature review highlights the challenges of modernizing the national economy in the context of globalization, as well as the advantages of TNCs and participation in global value chains (GVCs). However, the question of the connection between catchup development and transnationalization of local business, especially small and medium-sized ones, has been understudied. The novelty of the study is in the analysis of the sectoral and geographical structure of the foreign activities of Chinese TNCs and the analysis of the problems of the participation of Chinese TNCs in Western global value chains (GVCs). The main findings reveal that the creation of SMFAs is a response to the challenges of globalization, which impede the modernization of the Chinese economy. Powerful state support to SMFAs makes them dependent, and thus the government is able to direct the goals of private enterprises in accordance with the national interests. The major field of Chinese SMFAs is the promotion of products manufactured in the PRC in the American and European markets, and it contributes to the development of the national innovation system, redistributes the added value in favor of national manufacturers, and stimulates the development of hightech industries of the PRC. In developing countries SMFAs are represented by trade and manufacturing outlets within the “Belt and Road Initiative” They come after the infrastructural projects of large business, grouped in clusters, have strong coordination with other Chinese TNCs, and create Chinese GVCs. The main role of Chinese SMFAs in the modernization of the PRC economy is to ensure national interests, including industrial sovereignty and the growth of wellbeing of citizens as the basis of innovative demand. In the modern international labor division, this is achieved by a shift to high valueadded operations, accompanied by a struggle for the markets of developed countries and for sites for the low valueadded operations inside Chinese GVCs in developing countries.